Identifying and addressing challenges in pediatric antibiotic therapy: A review of current practices and recommendations - Ribeiro, Felipe Silva; Soares, Quimilda Gabriela Machados de Castro Alves Pontes; Querido , Jéssica Alves; Filho, Demócrito Andrade Costa; Bueno, Danielle Ribeiro; Dias, Isabella Nepomuceno; Pacheco, Gabriel Gonçalves; Fries , Davi Sousa; Lima, Luma Crys Pinheiro; Pessoa, Lucas Cerqueira; Rebêlo, Marilda Rodrigues; Silva , Alice Maria da (Seven Editora, 2023)
Introduction: The use of antibiotics in pediatric populations, especially in neonates, represents a significant challenge for health professionals due to the increased vulnerability of neonates to infections and possible consequences if antibiotics are not administered. However, current practices and recommendations for pediatric antibiotic therapy are often inadequate and rely on data extrapolated from adult studies, failing to consider pediatrics-specific factors. Objective: In this review, we examine the challenges related to pediatric antibiotic therapy. We address the use of antibiotics in neonatal intensive care units (NICUs), the risks of negative outcomes resulting from inappropriate and prolonged use of antibiotics, the lack of scientific basis to support recommendations on the duration of therapy, and particular issues related to the NICU. Methodology: This review examines challenges in pediatric antibiotic therapy through comprehensive research in medical databases. Selected studies, including epidemiology, reviews, and professional opinions, reveal problems such as antibiotic overuse and a lack of solid guidelines for duration of therapy. Limitations in the literature, such as the absence of specific studies and robust guidelines for NICUs, have been identified. Discussion:  The article demonstrates that the duration of antibiotic therapy for pediatric conditions is limited and variable, and the exact duration of antibiotic therapy for certain conditions is inaccurate. Results: It is crucial to address current gaps in knowledge by researching clinical parameters that can accurately stratify the severity of CAP and make them more sensitive and specific, as well as educating pediatric medical residents to ensure the safe and effective use of antibiotics. In addition, the existing antibiotic arsenal and the potential danger of long-term antibiotic use in neonates should be taken into account. Issues such as culture-negative LOS in premature infants and empirical use of antibiotics to "exclude" are major contributors to the overall use of antibiotics in neonatal units, and strategies for safe antibiotic restriction are difficult to identify and implement. Conclusion: Future research should focus on developing more accurate and effective diagnostic and therapeutic strategies for pediatric antibiotic therapy, as well as on identifying safe and effective strategies for antibiotic restriction in neonatal units. Overall, the results of this review highlight the need for ongoing research and education to improve pediatric antibiotic therapy practices and address the challenges associated with its use. DOI:https://doi.org/10.56238/innovhealthknow-007